Judicial interventions in health policy: Epistemic competence and the courts - Morales, Leticia (Bioethics, 2021)
The judiciary is a key policy actor that is involved in deciding health rights and policy by intervening in the policy process through a variety of judicial mechanisms, yet the appropriate extent of its involvement remains contentious. Taking the competence objection seriously requires understanding it as an epistemic problem about how courts assess empirical and scientific evidence in order to competently adjudicate controversial health claims. This paper examines recent advances in social epistemology to develop insights for the epistemic competence of the judiciary from a system-oriented approach. I outline three epistemic features that set the judiciary and the judicial decision-making process apart from other types of decision-makers in health policy: the distribution of epistemic power, the epistemic authority of a justified believer, and the principle of disinterestedness. Finally, I relate these insights back to the judicial decision-making process with a specific focus on recent court decisions in health rights and health policy in Chile.